Lip Morphological Changes and Differences before and after Orthodontic Treatment - Islam, MR; Kitahara, T; Naher, L; Nakasima, A; Takahashi, I (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Objectives: The objective of this study is to test the hypothesis that there is a difference in the morphology of the lips of Class II div 1 and Class III malocclusion, before and after orthodontic treatment. Methods: The sample subjects included 20 adult female patients with Angle Class II div 1 malocclusion and 30 adult female patients with dento-skeletal Class III malocclusion. Frontal photographs were taken both before and after orthodontic and/or orthognathic treatment. Thirty-five landmarks were placed on each tracing made from the photograph. Thereafter, landmarks were digitized into an x and y coordinates system with the subnasal point as the origin. The Class II pretreatment and posttreatment groups of rest and smile conditions were compared with the Class III group respectively, using t-tests. Results: In the Class II pretreatment group, upper and lower lips positioned downward than that in the Class III group. When smiling, there was no statistically significant difference between the two groups before treatment, whereas after orthodontic treatment both Class II and Class III groups showed the significant difference at rest and on smiling conditions. On smiling condition Class III group showed more upwards and lateral movement of the mouth corners than Class II group. Conclusion: Orthodontic treatment induced larger amount in movement of lips at smiling in both Class II and III patients, which may reflect the emotional changes in the patients after treatment. DOI: http://dx.doi.org/10.3329/bjodfo.v1i1.15971 Ban J Orthod & Dentofac Orthop, October 2010; Vol-1, No.1, 5-12